THE ANTIHERO IN CHBOSKY’S THE PERKS OF BEING A WALLFLOWER MOVIE - Dinda Siti Rodiyanti Pane; Sri Minda Murni (State University of Medan, 2015)
This study deals with the antihero in Chbosky’s The Perks of Being a Wallflowermovie. The objectives of this study are to find out antihero characterizations of themain character and to describe the author’s ways to present antiherocharacterizations. Descriptive qualitative method was applied in analyzing thedata and documentary technique was used in order to help collect the data relatedto the topic. The analysis shows that Charlie Kelmeckis as the main character ofthe movie is considered as an antihero as he owns four antihero characterizations;(a) Passive, (b) Dishonest, (c) Lonely, (d) Fragile. In presenting thosecharacterizations, the author used telling method and showing method.